Bioactive compositions in guava (Psidium guajava) at different stages of maturation in arid conditions - SINGH, AKATH; PANWAR, N R; MEGHWAL, P R; KHAPTE, P S; BERWAL, MUKESH K (The Indian Journal of Agricultural Sciences, 2019)
The bioactive compounds, total antioxidant activity and minerals in white, pink and red flesh guava (Psidium guajava L.) varieties were assessed and quantified at three different stages of maturity in arid conditions. Changes in pectin content followed similar trend as fruit firmness and it gradually decreased till ripe stage. Total soluble solids and total sugars increased till full ripe stage but reverse was case for acidity. Ascorbic acid in white flesh guava varieties increased till colour turning stage and then after it decreased, while in coloured varieties it showed decreasing trend till ripe stage. White flesh varieties contains negligible quantity of anthocyanin, lycopene and total carotenoid while pink flesh (Lalit) had highest concentration of these compound followed by red flesh (Red flesh). Total phenols and total antioxidant activities of guava fruits were comparatively low during green mature stage and it increased progressively in later stages. Flesh colour did not show any definite pattern on phenolic content and total antioxidant activities. Phenols was recorded highest in Allahabad Safeda, while total antioxidant activities in Lalit. Stage of maturation showed variable changes in mineral contents in guava varieties. It can be inferred from the present study that the remarkable metabolic changes occur between mature green to colour turning stage.